Striving for Excellence: An Analysis of Opportunities and Challenges in the English Language Curricula Reform in the UAE - Al-Shammari, Huda (2020)
High school graduates with good English language proficiency are key to the UAE’s future, yet many lack the level of English required for entry into university. In response, the Abu Dhabi Department of Education and Knowledge (ADEK) introduced a new high school curriculum “English Continuous Assessment Rich Task (ECART)” to support teaching of English as a Foreign Language (EFL), and then replaced it with another “National English Language Curriculum” by the Ministry of Education (MOE). This study conducts a comparative analysis of the English Continuous Assessment Rich Task (ECART) and the Ministry of Education’s (MOE’s) High School English Language curricula, examining their philosophies, content, and approaches to design, implementation, and assessment. The research is designed to explore how both theory and ideological classification can illuminate our understanding of the UAE English curriculum. The research question includes the following three areas of research: an examination of the key stakeholders’ perceptions/beliefs about the English language curriculum, the key themes that underlying the MOE and ECART curricula, and the main characteristics of the English language curriculum in the UAE before and after the reforms. An examination of the key issues and underlying themes indicates that both the ECART and MOE curricula were introduced to address challenges facing the acquisition of English for the world stage. The students were for the most part of a similar culture and background. In the MOE curriculum, the issue of preserving Emirati heritage and culture was more important than in the ECART curriculum. The ECART curriculum in contrast stressed the need to learn independent research skills in English while the MOE curriculum strengthened the stress on traditional assessment methods such as final tests. A recommendation would be to seek to attempt once more allowing students to define their own assessments (a hallmark of ECART) within the more highly structured MOE curriculum. Findings related to Schiro’s four framework ideologies indicate that the curricula showed clear differences, from the underlying intent to the learners’ final assessment. The MOE uses government-issue textbooks, prescribed assignments and related examinations; the ECART is more learner-centred with teachers and students designing the learning. The ECART sees English as a world language and students as researchers; the MOE includes more Emirati heritage and culture content, to support the UAE internationally. With respect to stakeholders’ beliefs, data concerning teacher’s stated beliefs and experiences found more than half the teachers willing to try new methods despite their own learning experiences where their teachers were ‘sages on the stage’. Finally, the study recommends more integrated professional development and the creation of communities of practice for teachers. In addition, it is recommended that further study of students’ performance in higher and further education especially focused on their willingness to leave their comfort zone. The use of activity theory as a lense, pointed to rich data in that the ECART involved teachers leaving the familiar teacher-centred and textbook-driven classroom; the MOE it was suggested fits better with their experiences and beliefs. The study demonstrates that the use of activity theory is helpful in comparing and contrasting curricula. The ‘activity system dynamics’ is especially useful in uncovering innovative approaches, in this case the ECART focus on project work. The success or lack thereof of the implementation of an innovative curriculum and the challenges teachers faced was uncovered with activity theory. It is recommended, therefore, that activity theory be used to help understand the evolution of MOE curriculum as part of a future longitudinal study.